The Use of Evidence-Informed Deliberative Processes for Health Insurance Benefit Package Revision in Iran - Mojtaba Nouhi; Rob Baltussen; Seyed Sajad Razavi; Leon Bijlmakers; Mohammad Ali Sahraian; Zahra Goudarzi; Parisa Farokhian; Jamaleddin Khedmati; Reza Jahangiri; Alireza Olyaeemanesh (Kerman University of Medical Sciences, 2022)
Background  Iran considers the revision of its health insurance benefit package (HIBP) as a means to achieve universal health coverage (UHC). Yet, its decision-making process has been criticised for being weak in terms of accountability and transparency. This paper reports on the development and implementation of the HIBP revision in Iran in the period 2019-2021, employing evidence-informed deliberative processes (EDPs), a framework for benefit package design with the explicit aim of optimising the legitimacy of decision-making.Methods  The High Council for Health Insurance (HCHI) is coordinating the HIBP revision: it planned the six steps of the EDP framework with support from World Health Organization (WHO) and Radboudumc in 2019, and conducted a pilot project on multiple sclerosis (MS) diagnosis and treatment in 2020.Results  Implementation of the MS pilot project concerned the installation of advisory committees (involving some 60 stakeholders in supportive task forces, a technical working group [TWG] and a national advisory committee [NAC]), the selection of decision criteria (relating to quality of care, necessity, and sustainability), the inclusion of services for evaluation (nine in total), and the assessment and appraisal of these services.Conclusion  Implementation of the priority setting process for MS diagnosis and treatment services has likely improved the legitimacy of decision-making by involving stakeholders who engaged in deliberation based on available evidence in a stepwise, transparent process. It is expected to improve the quality of care for MS patients as well as its financial accessibility, at a zero net budget impact. The pilot project has served to help Iran's health system move faster toward UHC for a broader range of essential health services.